The Correlation between Secondary Students' Reading Anxiety and Their Reading Comprehension - Rohman, Fahim Fatur (Universitas Negeri Surabaya, 2023)
This quantitative study has a purpose to find the correlation between secondary students reading anxiety and their reading comprehension. The participants were 49 secondary students from one of the vocational high schools in Sidoarjo. The correlational design was used in this research. In data collecting, the researcher used a questionnaire adapted from FLRAS (Foreign Language Reading Anxiety Scale) by Saito (1999). To gather reading comprehension scores, researchers use the TOEFL Junior Reading Test from www.ets.org and use the CEFR scoring method as the assessment. This study was conducted in the pandemic situation, so researchers use Google Form as an online platform to gain the data. The result shows that most secondary students experience reading anxiety in the medium level with a total of 70,8% students. The result also revealed that secondary students’ reading anxiety and reading comprehension was negatively correlated. The significance level of correlation was (r = -0,396). Thus, the significance level of correlation is categorized as low correlation.